Continuously tunable wavelength output from an Er-doped fiber femtosecond optical frequency comb with single-point frequency-doubling technique. (22nd June 2015) - Liu, H; Cao, S Y; Meng, F; Lin, B K; Fang, Z J
Abstract: Femtosecond optical frequency combs (FOFCs) with wavelengths covering the visible range have potential applications in the absolute frequency measurement of iodine-stabilized lasers and optical clock lasers. In this paper, an Er-FOFC with a tunable wavelength output from 689 to 813 nm based on the single-point frequency-doubling technique is demonstrated. Meanwhile, a beat frequency signal between the Er-FOFC and a tested laser at 729 nm with a signal-to-noise ratio of 30 dB at a resolution bandwidth of 100 kHz is obtained.